Superior low-cycle fatigue properties of CoCrNi compared to CoCrFeMnNi. (15th March 2021) - Lu, Kaiju; Chauhan, Ankur; Walter, Mario; Tirunilai, Aditya Srinivasan; Schneider, Mike; Laplanche, Guillaume; Freudenberger, Jens; Kauffmann, Alexander; Heilmaier, Martin; Aktaa, Jarir
Abstract: We report on the low-cycle fatigue behavior of single-phase, face-centered cubic CoCrNi and CoCrFeMnNi at room temperature. Both alloys manifest cyclic hardening followed by softening and a near steady state until failure. CoCrNi exhibits higher strength, lower inelastic-strain, and longer lifetime than CoCrFeMnNi. For both alloys, microstructural investigations reveal no noticeable changes of texture, grain size and twin fraction. Nevertheless, CoCrNi exhibits planar dislocation structures, while CoCrFeMnNi shows well-defined wavy dislocation structures. This is due to CoCrNi lower stacking fault energy, which enhances planar slip and delays deformation localization leading to its superior fatigue resistance, compared to CoCrFeMnNi. Graphical abstract: Image, graphical abstract